Field Measurements of Vibration on the Car Body-Suspended Equipment for High-Speed Rail Vehicles - Jinying Guo; Huailong Shi; Fansong Li; Pingbo Wu (Shock and Vibration)
The vibrations in the flexible car bodies of the high-speed electric multiple units (EMUs) and their coupling effects with the bogies and other types of equipment vibrating have lead issues for railway operators and gained interest for researchers. Other than a numerical investigation, field measurements on the vibrating characteristics of the car body (CB) and its suspended equipment (CBSE) for a high-speed railway vehicle were performed to elaborate the vibrating characteristics on the CB and its CBSE. In this long-term tracking test, the running stability of vehicle and wheel-rail interaction were also examined with the increase of operation distance (OD), a total of 2,400,000 km. The test configuration and arrangements are introduced first, followed by the data analysis in time and frequency domains. It is seen that the wheelset conicity increases 0.008 per 10,000 km, which increases approximately linearly with the OD from 0.10 to 0.40. Two types of wheel treads, S1002CN and LMB10, have different ranges in conicity and reprofiling cycles. The lateral accelerations on CB in a downward-running case (0.5 g) are much greater than that in upward-running case (0.2 g) corresponding to the vehicle stability differences. The 15 Hz low-pass filtered acceleration on CB experiences a maximum of 0.10 g and an averaged amplitude around 0.05 g, whereas the frequency spectrum has peaks of 0.01 g on CB and 0.1 g on CBSE. It states that an elastic suspension between the CBSE and the CB prevents the high-frequency vibration from the CB.